2011
DOI: 10.1016/j.watres.2011.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Fate of the pathogen indicators phage ΦX174 and Ascaris suum eggs during the production of struvite fertilizer from source-separated urine

Abstract: (T. Kohn).A v a i l a b l e a t w w w . s c i e n c e d i r e c t . c o m j o u r n a l h o m e p a g e : w w w . e l s e v i e r . c o m / l o c a t e / w a t r e s w a t e r r e s e a r c h 4 5 ( 2 0 1 1 ) 4 9 6 0 e4 9 7 2 0043-1354/$ e see front matter ª

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 47 publications
2
58
0
Order By: Relevance
“…In the porewater, parameters of interest are the pH, ionic strength and the concentration of NH 3 , which is a known biocide. Decrey et al 16 performed a simulation of these parameters as a function of moisture reduction in struvite (at 35°C , Low RH). The NH 3 concentration declines rapidly with moisture, and the pH approaches neutral.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the porewater, parameters of interest are the pH, ionic strength and the concentration of NH 3 , which is a known biocide. Decrey et al 16 performed a simulation of these parameters as a function of moisture reduction in struvite (at 35°C , Low RH). The NH 3 concentration declines rapidly with moisture, and the pH approaches neutral.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For laboratory-scale experiments, each struvite cake was produced in sterile reactors as previously described from 1 L of urine by adding 1.5 g MgCl 2 ·6H 2 O (Acros Organics, Geel, Belgium), gently stirring for 10 min, and filtering through a nylon filter (pore diameter ≅ 18−240 μm) cut to fit the filtration unit (45 mm diameter) using a manual pump. 16 For pilot-scale experiments, four struvite batches were produced from reactors built and maintained by EWS. 9 Urine storage tanks were mixed with a peristaltic pump prior to being pumped into the reactor.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoglund also found with rotavirus, a double stranded RNA virus, inactivation occurred during specific conditions, greater than 20˚C and longer than one month storage, increasing the necessity for storage or sterilization before use. Recovery of struvite from source-separated urine has revealed accumulation of pathogens can occur, with partial inactivation occurring with application of product heat and drying (Decrey et al 2011). …”
Section: Contaminantsmentioning
confidence: 99%
“…Investigation into struvite precipitated from source-separated urine dosed with bacteriophage PhiX174 and Ascaris suum eggs indicated an inclusion of both (Decrey et al 2011). Decrey also observed that drying struvite using heat can increase the inactivation of pathogens, decreasing associated concern of inclusion.…”
Section: Contaminantsmentioning
confidence: 99%